Germline genetic variants of the renin-angiotensin system, hypoxia and angiogenesis in non-small cell lung cancer progression: Discovery and validation studies - Catarata, MJ (2020)
Introduction: The renin–angiotensin system (RAS) is involved in cell proliferation, immunoinflammatory response, hypoxia and angiogenesis, which are critical biological processes in lung cancer. Our aim was to study the association of putatively functional genetic polymorphisms in genes coding for proteins involved in RAS, hypoxia and angiogenesis with non-small cell lung cancer (NSCLC) prognosis. Methods: Genotyping of 52 germline variants from genes of the RAS and hypoxic/angiogenic factors/receptors was performed using MassARRAY iPLEX Gold in a retrospective cohort (n = 167) of advanced NSCLC patients. Validation of the resulting genetic markers was conducted in an independent group (n = 190), matched by clinicopathological characteristics. Results: Multivariate analysis on the discovery set revealed that MME rs701109 C carriers were protected from disease progression in comparison with homozygous T (hazard ratio (HR) = 0.5, 95% confidence interval (CI) = 0.2–0.8, p = 0.010). Homozygous A and T genotypes for KDR rs1870377 were at increased risk for disease progression and death compared to heterozygous (HR = 1.7, 95% CI = 1.2–2.5, p = 0.005 and HR = 2.1, 95% CI = 1.2–3.4, p = 0.006, respectively). Carriers of homozygous genotypes for ACE2 rs908004 presented increased risk for disease progression, only in the subgroup of patients without tumour actionable driver mutations (HR = 2.9, 95% CI = 1.3–6.3, p = 0.010). Importantly, the association of homozygous genotypes in MME rs701109 with risk for disease progression was confirmed after multivariate analysis in the validation set. Conclusion: This study provides evidence that MME polymorphism, which encodes neprilysin, may modulate progression-free survival in advanced NSCLC. Present genetic variation findings will foster basic, translational, and clinical research on their role in NSCLC.